Becoming a teacher behind the walls: children through the eyes of early childhood teachers in penitentiary institutions - Erol, Mustafa; Erol, Ahmet; Aytekin, Mehmet Sukru; Selcuk Ozdemir, Tugba (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
In T & uuml;rkiye, the Ministry of Justice and the Ministry of National Education signed a protocol to support children living with their mothers in prisons and detention centers. Through this cooperation, justice kindergartens have been opened for children aged 3-5 who are living with their mothers. Teachers have been employed in these kindergartens, and educational activities have begun. In this context, the study has two primary objectives. First, to reveal the experiences of preschool teachers working in prison preschools, and second, to examine the impact of the prison environment on children through the teachers' perspectives. The study was conducted with fifteen preschool teachers working in nine different prison preschool education institutions located in different provinces of T & uuml;rkiye. Data for this study, conducted using a phenomenological design, were collected through semi-structured interviews. The data were analyzed using a content analysis approach. The research findings revealed that the experiences of preschool teachers working in prison preschools present both professional opportunities and significant challenges. Teachers stated that while they gained experience, the limited conditions of the prison environment, lack of family involvement, and witnessing children's traumatic life stories led to emotional strain. For children, adverse social environments, insufficient stimulation, and behavioral problems are prominent risks. These results suggest that prison preschools need to be strengthened with support mechanisms for both children and teachers.
Keywords: Prison kindergarten; teacher experiences; early childhood education; INCARCERATED MOTHERS; CHALLENGES; OUTCOMES; Criminology & Penology; Psychiatry